Notes on the genus Diestramima Storozhenko, 1990 (Orthoptera, Rhaphidophoridae) with description of three new species from China - Qidi Zhu; Hao Xu; Ruigang Yang; Fuming Shi (ZooKeys)
Three new species of the genus Diestramima are described from China: Diestramima ligula Zhu & Shi, sp. nov., Diestramima longzhouensis Zhu & Shi, sp. nov., and Diestramima napoensis Zhu & Shi, sp. nov. Moreover, the females of Diestramima parabispinosa Qin, Wang, Liu & Li, 2016 and Diestramima distincta Gorochov, 2010 are described for the first time. Images illustrating the morphology of these species are provided.